1987
DOI: 10.1093/ageing/16.4.208
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Continued or Rebleeding and Death From Gastrointestinal Haemorrhage in the Elderly

Abstract: We analysed 103 episodes of upper gastrointestinal bleeding in 88 elderly patients (age 76 +/- 7.7 years) to determine which of a group of 52 clinical and laboratory variables, measured on admission, best predicted continued or rebleeding, and death in these patients. Variables which related directly to the size of the bleed (blood urea, haemoglobin, pulse rate, systolic blood pressure) were all strongly predictive of both outcomes (P less than 0.001). Of the variables unrelated to the size of the bleed, prolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The single postoperative death was not attributable directly to surgery or peptic ulcer disease. Risk factors for operative mortality are well publicized 2–9 . In general, there are four broad categories of patients with peptic ulcer disease who need early surgical intervention: those with previous history of UGIH, those actively bleeding from a gastric or duodenal ulcer, especially with a visible blood vessel in an ulcer crater, those requiring 6 or more units of blood in the first 24 hours, and those with onset of hemorrhagic shock despite adequate resuscitation.…”
Section: Discussionmentioning
confidence: 99%
“…The single postoperative death was not attributable directly to surgery or peptic ulcer disease. Risk factors for operative mortality are well publicized 2–9 . In general, there are four broad categories of patients with peptic ulcer disease who need early surgical intervention: those with previous history of UGIH, those actively bleeding from a gastric or duodenal ulcer, especially with a visible blood vessel in an ulcer crater, those requiring 6 or more units of blood in the first 24 hours, and those with onset of hemorrhagic shock despite adequate resuscitation.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary artery disease (CAD), chronic liver disease, large varices, those undergoing endotherapy, renal failure, low Hb, high pulse rate, low systolic blood pressure, increased INR, those in need of blood transfusion, and Rockall score of >3 were significant predictive factors in rebleeders as compared to non-rebleeders. Booker et al [ 16 ] also reported that renal failure, low Hb, high pulse rate, low systolic blood pressure, prolonged PT, and elevated serum creatinine were strong predictors of rebleed.…”
Section: Discussionmentioning
confidence: 99%